HUBUNGAN ANTARA FAKTOR RISIKO TAK TERKONTROL DAN KEJADIAN STROKE ISKEMIK BERULANG - Pukovisa Prawiroharjo*, Wiji Lestari**, Salim Harris* (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION HYPERTENSION DIABETES MELLITUS DM ATRIAL FIBRILLATION OTHER HEART DISEASES OBESITY HIPERURICEMIA SMOKING AND POLYCYTEMIA HAVE BEEN INVESTIGATED AS RISK FACTORS OF FIRST AND ALSO RECURRENT ISCHEMIC STROKE EVENTS IN INTENTION TO PREVENT SECONDARILY FROM RECURRENT ISCHEMIC STROKE CONTROLLING THOSE RISK FACTORS IS VERY IMPORTANT THERE WERE NO AVAILABLE STUDY ESPECIALLY IN INDONESIA WHICH INVESTIGATES CONTROLLING EACH RISK FACTORS AND AS CUMULATIVE WITH RECURRENT ISCHEMIC STROKE EVENTS